Spacial Economic Model of Sustainability Scuba Diving Tourism at Gili Matra Conservation Area, Indonesia - Lalu Solihin; Tiridoyo Kusumastanto; Akhmad Fauzi; Fredinan Yulianda (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
The development of the marine tourism sector in conservation areas creates a dilemma in its management. When economic interests are prioritized, it will have a negative impact on ecological aspects, so it is necessary to have a balance between environmental conservation activities and tourist activities. Therefore, the purpose of this study is to design a sustainable tourist allocation management model in conservation areas and the optimal economic value of each dive tourism site. The results of the analysis of the carrying capacity of the area per dive location point are then analyzed using dynamic models to predict the growth in tourism demand and supply, so that the economic value of each dive tourism site can be known. The results of the analysis show that not all conservation areas are suitable for diving tourism sites and appropriate locations have varying carrying capacities, depending on the area of the area. The number of offers from each dive tourism location some are more than the capacity and some are still below the capacity, so that in order to achieve sustainable diving tourism management, the allocation of requests is carried out proportionally and does not exceed the level of the area's carrying capacity (supply).